SIRT1-mediated deacetylation of FOXO3 enhances mitophagy and drives hormone resistance in endometrial cancer - Xuehua Wei; Xiangpeng Xiong; Pingping Wang; Shufang Zhang; Dongxian Peng (BMC, 2024)
Abstract Background The complex interplay between Sirtuin 1 (SIRT1) and FOXO3 in endometrial cancer (EC) remains understudied. This research aims to unravel the interactions of deacetylase SIRT1 and transcription factor FOXO3 in EC, focusing on their impact on mitophagy and hormone resistance. Methods High-throughput sequencing, cell experiments, and bioinformatics tools were employed to investigate the roles and interactions of SIRT1 and FOXO3 in EC. Co-immunoprecipitation (Co-IP) assay was used to assess the interaction between SIRT1 and FOXO3 in RL95-2 cells. Functional assays were used to assess cell viability, proliferation, migration, invasion, apoptosis, and the expression of related genes and proteins. A mouse model of EC was established to evaluate tumor growth and hormone resistance under different interventions. Immunohistochemistry and TUNEL assays were used to assess protein expression and apoptosis in tumor tissues. Results High-throughput transcriptome sequencing revealed a close association between SIRT1, FOXO3, and EC development. Co-IP showed a protein-protein interaction between SIRT1 and FOXO3. Overexpression of SIRT1 enhanced FOXO3 deacetylation and activity, promoting BNIP3 transcription and PINK1/Parkin-mediated mitophagy, which in turn promoted cell proliferation, migration, invasion, and inhibited apoptosis in vitro, as well as increased tumor growth and hormone resistance in vivo. These findings highlighted SIRT1 as an upstream regulator and potential therapeutic target in EC. Conclusion This study reveals a novel molecular mechanism underlying the functional relevance of SIRT1 in regulating mitophagy and hormone resistance through the deacetylation of FOXO3 in EC, thereby providing valuable insights for new therapeutic strategies.